Garcinia isthmensis (Clusiaceae): a new tree species for Central America - Mouzinho, Thiago; Carrión, Juan F.; Marinho, Lucas Cardoso; Giacomin, Leandro Lacerda (Phytotaxa, 2025)
We present a new species, Garcinia isthmensis Mouzinho, sp. nov. ined., known to occur in Costa Rica and Panama. Garcinia isthmensis is described and distribution data, photographs and preliminary conservation status are provided, as well as its diagnostic characteristics and morphological affinities.